Analisis Perbedaan Perilaku Keuangan Masyarakat Kecamatan Percut Sei Tuan Sebelum Dan Semasa Pandemi Covid-19 - Ade Gunawan; Dwi Arfilla (Maneggio: Jurnal Ilmiah Magister Manajemen, 2021)
The purpose of this study was to determine and analyze differences in the financial behavior of the people of Percut Sei Tuan District before and during the covid-19 pandemic. This study uses a comparative and descriptive approach with data collection techniques from the results of questionnaires/questionnaires. The number of samples used in this study were 100 respondents from the people of Percut Sei Tuan District. This study uses judgment sampling and uses data analysis techniques, namely Normality Test, Levene's Test Homogeneity of Variance, Paired Sample T Test, Wilcoxon Test, testing is carried out using the SPSS (Statistical Package For The Social Sciences) Software version 20 for windows. The results of this study state that there is a significant difference between financial behavior before and during the covid-19 pandemic in the people of Percut Sei Tuan District.